Rampy a další pomůcky pro nástup tělesně postižených do autobusů MHD - Pavlo, Matej (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Bakalárska práca prináša kritické zhodnotenie konštrukčných riešení pomôcok pre nástup telesne postihnutých do autobusov mestskej hromadnej dopravy a zároveň sa zaoberá návrhom niekoľkých variant výklopných rámp, ktoré sa snažia zlepšiť nedostatky súčasných rámp. Prvá časť obsahuje prehľad súčasnej situácie pomôcok pre nástup a výstup telesne hendikepovaných osôb. V druhej časti sa nachádzajú návrhy konštrukčných riešení, ktoré by sa mohli uplatniť v autobusoch mestskej hromadne dopravy. A v poslednej časti sú tieto návrhy zhodnotené a navzájom porovnané.

The bachelor work brings the critical assessment of the construction solutions of the aids for boarding of the physically handicapped persons in the busses of the municipal mass transportation and at the same time it deals with design of some tipping ramp variants, which try to improve the faults of the present ramps. The first part contains the review of the present situation of the aids for boarding and entrance of the physically handicapped persons. The second part contains the designs of the construction solutions, which could be of use in the busses of the municipal mass transportation. And in the last part are these designs reviewed and compared each other.
Ramps and other devices for the entrance of handicapped to the buses
Keywords: bezbariérová doprava; telesne postihnutý; rampa; zdvíhadlo; nízkopodlažný autobus; hliníková voština; Transportation without barriers; physically handicapped person; ramp; lift; low-floor bus; aluminium honeycomb